Celecoxib in arthritis: relative risk management profile and implications for patients - Gayle McKellar; Gurkirpal Singh (Dove Medical Press, 2009)
Gayle McKellar1, Gurkirpal Singh21Centre for Rheumatic Diseases, Glasgow Royal Infirmary, Glasgow, UK; 2Division of Gastroenterology and Hepatology, Stanford University School of Medicine, Palo Alto, CA, USAAbstract: Celecoxib is a selective cyclo-oxygenase 2 inhibitor licensed for use in musculoskeletal symptoms as well as in primary dysmenorrhea and acute pain. One advantage celecoxib has over traditional nonsteroidal anti-inflammatory drugs is that of significantly fewer gastrointestinal side-effects associated with its use. Much has been published on the potential cardiovascular and cerebrovascular complications of its administration. This review details the available evidence to allow prescribers to make informed decisions in the light of potentially conflicting evidence. The overall cardiovascular risk is increased with higher doses of celecoxib but is comparable with nonselective nonsteroidal anti-inflammatory use. As with all of these drugs, the potential cardiovascular and gastrointestinal risks of prescription need to be weighed up against possible benefits for each individual patient and discussed with the patients themselves.Keywords: arthritis, cardiovascular, celecoxib, gastrointestinal, nonsteroidal anti-inflammatory drugs, safety